Photogrammetric analysis of facial soft tissue profile of Iraqi adults sample with Class II div.1 and Class III malocclusion: (A comparative study) - Salam R Abd-Alwhab; Dhiaa J Nasir (College of Dentistry/ University of Baghdad, 2013)
Background: The purposes of this study were to determine the photogrammetric soft tissue facial profile measurements for Iraqi adults sample with class II div.1 and class III malocclusion using standardized photographic techniques and to verify the existence of possible gender differences. Materials & methods: Seventy five Iraqi adult subjects, 50 class II div.1 malocclusion (24 males and 26 females), 25 class III malocclusion (14 males and 11 females), with an age range from 18-25 years. Each individual was subjected to clinical examination and digital standardized right side photographic records were taken in the natural head position. The photographs were analyzed using AutoCAD program 2007 to measure the distances and angles used in the Soft Tissue Photogrammetric Analysis. Descriptive statistics was obtained for (29) measured variables for both genders and independent- samples t-test was performed to evaluate the genders difference. Results &conclusions: The results indicated that: males had greater facial heights and lengths as well as greater prominences of facial dimensions in class II div.1 and class III malocclusion. The mean values of all angular variables were higher in females than males in the class II div.1 exceptin the following angular measurements: vertical nasal angle,angle of the nasal dorsum,cervicomental angle andangle of the lower facial third,with larger male dimensions in all linear measurements of the nasal, lips, chin area and facial analysis except upper facial third.Independent t-testshowed statistically significant gender differences in the vertical nasal angle, nasal angle, nasofrontal angle; angle of the nasal dorsum; nasolabial angle, cervicomental angle, lower facial third, facial depth subnasal depth, nasal prominence, length of upper lip, length of lower lip of pogonion and height of chin,while in the class III malocclusionThe mean values of all angular variables were higher in males than females except in the following: nasofrontal angle, nasal angle,nasolabial angle,mentolabial angleandangle of the middle facial third with larger male dimensions in all linear measurements of the facial, lips, chin area and nose analysisexcept the height of nasal tip, nasofrontal angle, nasal angle, nasolabial angle, angle of total convexity, lower facial third, upper lip, upper lip, prominence of lower lip, prominence of chin and height of chin. Independent t-test showed statistically significant gender differences.